Daur Muʻallim fī at-Taʻlīm fi al-Madrasah al-Mutawassiṭah al-Ḥukūmiyyah al-Ūlā Jember - Zainuri Zainuri; M. Abdul Ghofur (Al-Fusha : Arabic Language Education Journal, 2021)
Teachers have a vital role in the success of student learning at Madrasah Tsanawiyah Negeri 1 Jember. Teachers need to have competence in teaching and educating. The purpose of this article was to describe the teacher's role as a source of knowledge, motivator, and learning model. This study used a phenomenological qualitative approach. Data collection methods were observation, interviews, and documentation. Research findings indicated that teachers hold most of the parts in the success of the teaching and learning process. The success of student learning was highly dependent on the role of the teacher. The teachers act as a source of information that they apply interested teaching-learning process and show students how to learn creatively and effectively.